A Comparative Study on Psychosocial Factors between Mothers of Infants with and without Physical Abnormalities - Mahtab Ranjbar; Ebrahim Masoudnia; Mohsen Haghshenas Mojaver (Journal of Holistic Nursing and Midwifery)
Abstract Introduction: Congenital anomalies are one of the most important causes of disability and mortality in childhood seen in developing and developed countries. Mothers with physically-abnormal newborns have unfavorable lifestyle compared to mothers with healthy infants. Objective: The aim of this study was to determine the difference between mothers of infants with and without physical abnormalities in terms of psychosocial factors. Materials and Methods: This is a case-control study with two study groups; the case group (n=133) consists of mothers who had babies with birth defects referred to health centers in Amol city, Iran for postnatal care in 2018. The control group (n=133) included mothers with healthy infants in this city. They were selected using a convenience sampling method. Measurement tools included a Socio-demographic form, Health-Promoting Lifestyle Profile (HPLP), Multidimensional Perceived Social Support Scale (MPSSS), Coping Strategies Scale - Short Form (CSS-SF), Prenatal Distress Questionnaire (PDQ), and General Health Questionnaire - Short Form (GHQ-SF). Data were analyzed using descriptive statistics, chi-square test, and t-test. Results: A total of 266 mothers with a mean age of 31.9±5.6 years were examined. There was a significant difference between the two groups of mothers in terms of overall HPLP score (P=0.01), and its dimensions of spiritual growth (P<0.05), physical activity, nutrition (P=0.01), and stress management (P<0.05). Moreover, a significant difference was reported between them in terms of MPSSS and its dimensions of social support from friends, family, and significant others (P=0.01). Furthermore, There was a significant difference between them with respect to GHQ dimensions of anxiety/insomnia, and depression (P<0.01); CSS dimensions of escape avoidance and emotion-focused coping strategies (P=0.01); and PDQ and its dimensions of concerns about the delivery and the health of the baby, and about the body weight/image (P=0.01). Conclusion: Mothers of infants with and without birth defects are significantly different from each other in terms of psychosocial factors. It seems that poor psychosocial variables in mothers during pregnancy can act as a risk factor for congenital anomalies.